2014
DOI: 10.4314/bajopas.v6i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Pedogenesis, weathering status and mineralogy of the soils on ironstone plateaux (laterites), Sokoto Nigeria

Abstract: Soils on four ironstone plateau near kalalawa, Adarawa, Bissalam and Tureta in Sokoto State were studied with the aim of a ascertaining their genesis, weathering status and soil mineral content. Morphological studies, total elemental analysis and X-ray diffraction were conducted for this purpose. The soils were found to have formed on weathered geological materials overlain by indurated ironstone crust. The geological weathered materials are Gwandu/kalambaina, Gwandu, Dange/Wurno and Gundumi formation on kalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
4
8
0
Order By: Relevance
“…Using World Reference Base (2014), the soils are classified as Ferric Lixisols and as Idesan series at local level. Yakubu and Ojanuga (2009) also obtained similar results in a similar study.…”
Section: Jb1 (Agerige)supporting
confidence: 78%
See 1 more Smart Citation
“…Using World Reference Base (2014), the soils are classified as Ferric Lixisols and as Idesan series at local level. Yakubu and Ojanuga (2009) also obtained similar results in a similar study.…”
Section: Jb1 (Agerige)supporting
confidence: 78%
“…Different soil properties encountered along landscapes will affect pattern of crop production, soil physical properties such as clay content distribution with depth and sand content which have been shown to be highly correlated with soil genesis while soil organic matter has been shown to vary with slope position (Miller et al, 1988). Other studies which support the current study have been documented (Yakubu and Ojanuga, 2009;Ojetade et al, 2014;Esu et al, 2014;Fasina et al, 2007a). Sharu et al (2013) reported that coupling of soil characterization and classification provides a powerful resource for benefit of mankind especially in the area of food security and environmental sustainability while, Lekwa et al (2004) reiterated that soil characterization provides the basic information necessary to create functional soil classification schemes and assess soil fertility in order to unravel some unique soil problems in an ecosystem.…”
Section: Introductionsupporting
confidence: 79%
“…The fact that banana yield is better correlated with the TRB or MR than the CEC or the sum of exchangeable bases (S) would be due to the fact that low values of CEC (or even those of S) are observed in less altered soils (with high primary minerals content) as well as in highly weathered soils. Conversely, TRB, MR, non-exchangeable cations and total fraction of cations, the silt content (Yakubu and Ojanuga, 2013) and banana yield values are higher in young soils than in very old soils and this explains the better correlation between those parameters. At the same time, this would indicate that the prediction of a soil potential production based only the routine analysis parameter, that is, the CEC or the sum of the bases is distorted and the distortion appears to be reduced when the results of total analysis are considered.…”
Section: Eahb Yield Potential As a Snapshot Of The Soil Inherent Propmentioning
confidence: 82%
“…Many studies have documented that the chemical composition of lysimetric water depends on the natural conditions -geology and hydrology of the land, soil type and climatic conditions, the form and amount of fertilizer used, and the processes of weathering (Atanassov et al, 1985;Meissner et al, 2010;Stoichev, 1997;Stoichev et al, 1996;Zhao, 2010). It is estimated that the rate of weathering of various minerals is a function of export of dissolved chemical elements draining the soil profile and are determined by the mineral and chemical composition of soil forming rocks (Chadwick and Chorover, 2001;Taylor and Velbel, 1991;Yakubu and Ojanuga, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have documented that the chemical composition of lysimetric water depends on the natural conditions -geology and hydrology of the land, soil type and climatic conditions, the form and amount of fertilizer used, and the processes of weathering (Atanassov et al, 1985;Meissner et al, 2010;Stoichev, 1997;Stoichev et al, 1996;Zhao, 2010). It is estimated that the rate of weathering of various minerals is a function of export of dissolved chemical elements draining the soil profile and are determined by the mineral and chemical composition of soil forming rocks (Chadwick and Chorover, 2001;Taylor and Velbel, 1991;Yakubu and Ojanuga, 2013).Some studies have been made on the climatic factors and changes that have a great impact on pedogenic weathering of minerals (White and Blum, 1995). Therefore (Atanassov, 1977), data on the content and migration of nutrients with infiltration water can provide objective information about the nature and trends in the weathering processes of soil minerals as a result of anthropogenic loading.…”
mentioning
confidence: 99%